2015 International Conference on Advances in Computing, Communications and Informatics (ICACCI) 2015
DOI: 10.1109/icacci.2015.7275726
|View full text |Cite
|
Sign up to set email alerts
|

Learners and educators attitudes towards mobile learning in higher education: State of the art

Abstract: In the last few years, the way we learn has been significantly changed from traditional classrooms that depend on printed papers into e-learning relying on electronic teaching material. Contemporary educational technologies attempt to facilitate the delivery of learning from instructors to students in a more flexible and comfortable way. Mobile learning (M-learning) is one of such pervasive technologies that has been evolved rapidly to deliver e-learning using personal electronic devices without posing any res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…Through the increased availability, sophistication and use of mobile devices, m-learning has the potential to offer improved efficiency and effectiveness in teaching and learning, alongside improved learning outcomes and employability skills (Cochrane, 2011;Conde, Muñoz, & García, 2008;Fuller & Joynes, 2015). For example, studies describing the benefits of tablet computers illustrate positive student perception of the learning environment created by the devices, as well as positive effects on students' performance (Al-Emran & Shaalan, 2015;Enriquez, 2010;Morris et al, 2016). Pimmer, Mateescu, and Gröhbiel's (2016) review of 36 empirical studies of the outcomes associated with mobile and ubiquitous learning confirmed previous reviews that the majority of studies have found positive effects on learning, although they do add that most studies in this area are limited in that they involve the use of mobile learning as an instructionist approach.…”
Section: Mobile Learningmentioning
confidence: 99%
“…Through the increased availability, sophistication and use of mobile devices, m-learning has the potential to offer improved efficiency and effectiveness in teaching and learning, alongside improved learning outcomes and employability skills (Cochrane, 2011;Conde, Muñoz, & García, 2008;Fuller & Joynes, 2015). For example, studies describing the benefits of tablet computers illustrate positive student perception of the learning environment created by the devices, as well as positive effects on students' performance (Al-Emran & Shaalan, 2015;Enriquez, 2010;Morris et al, 2016). Pimmer, Mateescu, and Gröhbiel's (2016) review of 36 empirical studies of the outcomes associated with mobile and ubiquitous learning confirmed previous reviews that the majority of studies have found positive effects on learning, although they do add that most studies in this area are limited in that they involve the use of mobile learning as an instructionist approach.…”
Section: Mobile Learningmentioning
confidence: 99%
“…A study by [17] claimed that studying the attitudes toward any technology assist the decision makers to identify the shortcomings and strengths and contribute to the establishment of a reliable infrastructure. Al Buraimi University College (BUC) is one of the evolving colleges in Oman that is keen to provide reliable technologies to their staff and students; one of such technologies is the e-Evaluation system [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…M_learning is not a one-dimensional approximation and therefore must be observed/analyzed in all its dimensions; according to Al-Emran and Shaalan [9] m_learning has three dimensions: (1) technology mobility (hardware and software, in special augmented and virtual reality, with possibilities to be adapted for educational purposes to stimulate learning within and outside the classroom [10], (2) student and teacher mobility (this is related to the fact that today everyone has one or more mobile devices and is connected to the Internet) and (3) learning mobility / educational context (according to [11] it is necessary to integrate tools, pedagogical approaches, assessment techniques and teacher training).…”
Section: M_learningmentioning
confidence: 99%